TIM-3 and CEACAM1 are Prognostic Factors in Head and Neck Squamous Cell Carcinoma - Yang, Fan; Zeng, Ziqing; Li, Jing; Ren, Xiubao; Wei, Feng (Frontiers in Molecular Biosciences, 2021)
Background: T-cell Immunoglobulin and Mucin domain-containing molecule-3 (TIM-3) is an activation induced inhibitory molecule involved in immune tolerance. TIM-3 is expressed on activated T cells and its signaling on cytotoxic T cells leads to T cell exhaustion which is mediated by carcinoembryonic antigen-related cell adhesion molecule 1 (CEACAM1), another well-known molecule expressed on tumor tissues and/or tumor infiltrating lymphocytes (TILs). Methods: In the present study, we investigated TIM-3 and CEACAM1 immunohistochemical expression in 80 head and neck squamous cell carcinoma (HNSCC) specimens, linked to detailed outcome, clinic-pathological parameters. Here we reported scores and absolute counts of TIM-3+/CEACAM1+ TILs, and evaluated the expression of CEACAM1 on tumor tissues. Results: The results showed that more TIM-3+ TILs infiltration correlated with poorer overall survival (P＜0.001), as did the presence of CEACAM1 on cancer cells (P＜0.001) and CEACAM1+ TILs in tumor microenvironment (P=0.015). Multivariate Cox regression analysis revealed that high TIM-3+ TILs may be considered as an independent prognostic factor of poor disease outcome (hazard ratio, 2.066; 95% confidence interval, 1.027-4.159; P= 0.042), as well as cancer cells expressed CEACAM1 level (hazard ratio, 5.885; 95% confidence interval, 2.832-12.230; P＜ 0.001). Conclusions: Our results indicate that expression of TIM-3 and CEACAM1 may represent a highly dysfunctional population of T cells. Our current findings suggest both of them were valuable predicting markers that might provide help for clinicians to design effective immunotherapeutic regimen against head and neck carcinoma.